1987
DOI: 10.1007/bf02554783
|View full text |Cite
|
Sign up to set email alerts
|

The surgical risk of colectomy in patients with cirrhosis

Abstract: The records of 54 patients with documented cirrhosis who underwent colectomy between January 1970 and January 1984 were studied to assess the operative risk and to determine the preoperative predictive risk factors. In-hospital mortality was 24 percent (13 patients), and postoperative complications occurred in 48 percent (26 patients). The risk of surgical intervention was significantly increased if encephalopathy, ascites, anemia, or hypoalbuminemia was present before operation. A simple operative risk index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 7 publications
0
43
0
1
Order By: Relevance
“…Not surprising is that the length of hospital stay (up to 68%) and total hospital charges (up to 45%) were also increased compared to noncirrhotic patients [8]. Indeed, all authors focusing on this topic reported on an increased mortality rate in cirrhotic patients, which varied from 4 to 54% [7,8,13,14,15,16,17,18,19,20,21]. Csikesz et al [8] found that (dependent on the type of surgery: cholecystectomy, colectomy, coronary artery bypass grafting, abdominal aortic aneurysm repair) cirrhotic patients had a 3.4- to 8-fold increased risk of death, whereas those with cirrhosis along with portal hypertension experienced a 7.8- to 22.7-fold increased risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprising is that the length of hospital stay (up to 68%) and total hospital charges (up to 45%) were also increased compared to noncirrhotic patients [8]. Indeed, all authors focusing on this topic reported on an increased mortality rate in cirrhotic patients, which varied from 4 to 54% [7,8,13,14,15,16,17,18,19,20,21]. Csikesz et al [8] found that (dependent on the type of surgery: cholecystectomy, colectomy, coronary artery bypass grafting, abdominal aortic aneurysm repair) cirrhotic patients had a 3.4- to 8-fold increased risk of death, whereas those with cirrhosis along with portal hypertension experienced a 7.8- to 22.7-fold increased risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…Cirrhosis and PHT are increasingly frequent conditions and are acknowledged to be associated with increased surgical risk after abdominal operations (10). Many investigators have observed that patients with cirrhosis and PHT tend to be more likely to have grave postoperative complications after cholecystectomy, frequently leading to their eventual death (11,12). One study showed that open cholecystectomy for cirrhotic patients had an 11-fold risk of 30-day mortality compared to open cholecystectomy for noncirrhotic patients (13).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have published studies evaluating the healing of peptic ulcers in patients with hepatic cirrhosis 20 , but there are few studies on hepatic cirrhosis and anastomosis healing [21][22][23] . Patients with cirrhosis may require colonic anastomosis, which causes concern on the part of the surgeon 22 . This study evaluated the influence of hepatic cirrhosis on the healing of colonic anastomosis.…”
Section: Introductionmentioning
confidence: 99%